2004
DOI: 10.1002/art.20673
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of different statins in murine collagen‐induced arthritis

Abstract: Objective. Hydroxymethylglutaryl-coenzyme A reductase inhibitors (statins) are widely used lipidlowering agents. In addition to their well-known effect on cholesterol levels, statins have been reported to display antiinflammatory activities both in vitro and in vivo. In this context, in vivo prophylactic and therapeutic effects of simvastatin were recently demonstrated in mouse collagen-induced arthritis, a well-described experimental model for human rheumatoid arthritis (RA). The aim of this study was to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 40 publications
2
58
0
2
Order By: Relevance
“…T cell proliferation was also significantly suppressed in lymphocyte cultures from simvastatintreated animals. However, a more recent study did not replicate these findings using atorvastatin, rosuvastatin, or simvastatin (139).…”
Section: Abeles and Pillingermentioning
confidence: 85%
“…T cell proliferation was also significantly suppressed in lymphocyte cultures from simvastatintreated animals. However, a more recent study did not replicate these findings using atorvastatin, rosuvastatin, or simvastatin (139).…”
Section: Abeles and Pillingermentioning
confidence: 85%
“…Previous investigations have shown that statins have a wide range of effects on cells and tissues involved in inflammation (37); however, animal studies on the therapeutic effects of systemically delivered statins in inflammatory arthritis have yielded conflicting results (21)(22)(23). Although the statin doses used in the mouse models (up to 40 mg/kg per day [21,22], equivalent to a daily human dose of 3.25 mg/kg [40]) were higher than those used in standard therapy in humans (0.1-1.0 mg/kg per day) (41), the amount of drug reaching the joints may be low since statins are designed to act primarily in the liver (42). The disparity in the results of animal studies may be due to liverspecific pharmacokinetics and poor distribution of statins to bone and joints.…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting results have been obtained from studies using animal models of RA. While Leung et al (21) showed that intraperitoneal simvastatin was effective in alleviating collagen-induced arthritis (CIA) in mice, these findings were not replicated in a later study (22). More recently, Funk and colleagues (23) demonstrated a bone-protective effect of subcutaneous simvastatin in rats with streptococcal cell wall-induced arthritis.…”
mentioning
confidence: 99%
“…The dose range for simvastatin in human use is 20-80 mg/day for cardiovascular disease; statinrelated side eff ects such as myopathy are known to be dosagedependent (Escobar et al, 2008). Furthermore, in experimental studies high doses of simvastatin are reported to increase the risk of toxicity and mortality (Palmer et al, 2004). In the study by Palmer et al (2004) of statin eff ect in collagen-induced arthritis, the anti-infl ammatory activity of simvastatin was seen only after administration of 40 mg/kg; serious side eff ects were observed during treatment.…”
Section: Tablementioning
confidence: 99%
“…Furthermore, in experimental studies high doses of simvastatin are reported to increase the risk of toxicity and mortality (Palmer et al, 2004). In the study by Palmer et al (2004) of statin eff ect in collagen-induced arthritis, the anti-infl ammatory activity of simvastatin was seen only after administration of 40 mg/kg; serious side eff ects were observed during treatment. Only 7 of 18 mice completed therapy.…”
Section: Tablementioning
confidence: 99%